2013
DOI: 10.1097/ncc.0b013e3182693522
|View full text |Cite
|
Sign up to set email alerts
|

Personal Financial Effects of Multiple Myeloma and Its Treatment

Abstract: Background Improvements in some treatment programs for multiple myeloma (MM) are increasing survival. As patients live longer with MM as a chronic disease, the personal financial effects of MM treatment become a serious concern. Objective The objective of this study was to identify the personal financial effects of MM and its treatment in five areas: employment, disability, health/medical and life insurance, retirement, and out-of-pocket expenses. Methods We mailed a questionnaire about financial issues to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 25 publications
2
66
0
Order By: Relevance
“…In the present study, higher indirect costs were observed for patients on regimens containing at least one injectable drug compared with all‐oral RRMM regimens. In accordance with these findings, evidence suggests that the majority of patients with MM (71%) report at least some financial burden associated with their disease , and for patients with RRMM, the leading drivers of indirect costs are out‐of‐pocket expenses and costs associated with frequent office visits . Previous studies of patients with cancer show that indirect costs are influenced by route of administration of therapies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study, higher indirect costs were observed for patients on regimens containing at least one injectable drug compared with all‐oral RRMM regimens. In accordance with these findings, evidence suggests that the majority of patients with MM (71%) report at least some financial burden associated with their disease , and for patients with RRMM, the leading drivers of indirect costs are out‐of‐pocket expenses and costs associated with frequent office visits . Previous studies of patients with cancer show that indirect costs are influenced by route of administration of therapies.…”
Section: Discussionsupporting
confidence: 58%
“…A recent analysis of commercially insured patients with MM reported monthly mean patient out‐of‐pocket expenditures for MM‐directed drug therapy of $81, with $42 and $39 per month spent on injectable and oral therapies, respectively . In another study, 36% of patients with MM reported applying for financial assistance, and 21% borrowed money to pay for medications .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of LILAC participants were at least 65 years of age at the time of cancer diagnosis, meaning they would have been eligible for Medicare and probably less likely to be denied health insurance. Little comparable information exists in the literature; however, in a population of patients who underwent intensive treatment for multiple myeloma, Goodwin et al reported that 29% changed or lost insurance coverage, including 10% who were unable to obtain replacement insurance, and that although 70% had life insurance when they began treatment, 8% of those no longer had the same life insurance policy at study entry an average of 5 years after diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…Financial burdens can also impact treatment decisions, which can negatively impact outcomes . Having health insurance does not prevent survivors from experiencing cancer‐related financial burdens,—a cancer diagnosis can lead to changes in insurance status, increases in insurance premiums, and the inability to obtain or keep health or life insurance …”
Section: Introductionmentioning
confidence: 99%
“…Patients who used the most intense healthcare at baseline: those who previously had at least one hospitalization and one emergency care visit were notably more likely to have an ISS score of III compared with the overall population (44.4% vs 24.1%, respectively), more lytic bone lesions (>10, 58.9% vs 38.6%, respectively) and reported substantially lower EORTC Global Health, Physical Functioning, Role Functioning, Emotional Functioning, and Social Functioning scores as well as greater Pain, Fatigue and Appetite loss (Table ). The baseline HRQoL score differences were clinically relevant …”
Section: Resultsmentioning
confidence: 99%